2017
DOI: 10.1111/jphp.12801
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of human osteoblast cells (MG63) proliferation using decanoic acid and isopropyl amine fractions of Wattakaka volubilis leaves

Abstract: The results confirmed that the optimized fraction containing decanoic acid and isopropyl amine at particular concentration stimulated the proliferation of human osteoblast (MG63) cells. Hence, the optimized concentration of this compound from W. volubilis may used for treatment of bone related injuries externally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…(MG63) cells(Venugopal et al, 2017). The current study further validated that fatty acids can regulate the bone remodeling in FHN(Bani Hassan et al, 2019;Kishikawa et al, 2019).…”
supporting
confidence: 72%
“…(MG63) cells(Venugopal et al, 2017). The current study further validated that fatty acids can regulate the bone remodeling in FHN(Bani Hassan et al, 2019;Kishikawa et al, 2019).…”
supporting
confidence: 72%
“…Furthermore, capric acid inhibits the micellar growth in vitro of Candida albicans due to a resulting 0.20 of its fractionated inhibitory concentration index for 70% growth inhibition, which is considered significant [90] . It potentially impacts the stimulation of the human osteoblast (MG63) by using decanoic acid fractions from Wattakaka volubilis leaves [91] . Finally, caproic acid can be utilized to increase gene delivery without affecting biocompatibility [92] .…”
Section: Virgin Coconut Oil As An Adjunctive Treatment For Various Ailments 431 Virgin Coconut Oil As An Adjunctive Treatment For Variousmentioning
confidence: 99%
“…[ 90,91] Hexanoic acid Caproic acid 6:0 Caproic acid can be utilized to increase gene delivery and enhance the delivery of protein.…”
Section: Systematic Name Common Name Carbon Skeleton Established Therapeutic Uses Referencesmentioning
confidence: 99%
“…The details of phytochemicals used in this study such as extraction, characterization and identification can be seen in our previous report [19]. Phytochemical incorporated gelatin nanofibers were prepared using the electrospinning process.…”
Section: Preparation Of Nanofibrous Scaffoldmentioning
confidence: 99%
“…One of the most important medicinal plants widely used in an orthopaedic application is Wattakaka volubilis. In our previous study, we reported that the active phytochemical compounds present in W. volubilis leaves can potentially be used to increase cellular proliferation and ECM production in bone and cartilage cells under optimized dosage [19].…”
Section: Introductionmentioning
confidence: 99%